Intra- and interannual regional fidelity of Semipalmated Sandpipers (Calidris pusilla) during migratory stopover in the upper Bay of Fundy, Canada - Sarah G. Neima; Diana J. Hamilton; Cheri L. Gratto-Trevor; Julie Paquet (Avian Conservation and Ecology, 2020)
The Bay of Fundy, Canada is a critical migratory stopover for Semipalmated Sandpipers (Calidris pusilla) during fall migration. Recent ecological changes combined with range-wide population declines indicate that a re-evaluation of habitat use and regional fidelity is required. The Bay of Fundy is divided into three regions, each of which contains multiple foraging and roost sites. In this study, we examined local movement and regional fidelity within and between years using radio-telemetry and field-readable markers. We deployed 194 radio-transmitters and 2295 field-readable flags on Semipalmated Sandpipers during migration in 2013-2014, and resighted these birds, along with additional birds flagged in 2012, between 2013 and 2016. Radio-tracked birds used on average 1.3 to 4.1 foraging and roost sites per day, with most making multiple daily movements, but only 2% made permanent moves between geographically distant regions within the bay during stopover. Additionally, 97% of birds returned to their original region in subsequent years. The use of multiple sites suggests Semipalmated Sandpipers are capable of adapting to dynamic conditions in the Bay of Fundy on a local scale, but the high regional fidelity suggests that their ability to adapt to changes occurring at a regional scale may be limited. Uncertainty about the capability of Semipalmated Sandpipers to flexibly move among different regions of the Bay of Fundy supports the need for conservation at both the site and regional level.